The PACT study protocol: a time series study investigating the impact, acceptability and cost of an integrated model for psychosocial screening, care and treatment of patients with urological and head and neck cancers. Issue 1 (9th January 2014) - Girgis, Afaf; Kelly, Brian; Boyes, Allison; Haas, Marion; Viney, Rosalie; Descallar, Joseph; Candler, Hayley; Bellamy, Douglas; Proietto, Anthony
Abstract : Introduction: While there is good evidence of the effectiveness of a variety of interventions and services to prevent and/or relieve distress experienced by people affected by cancer, much of this psychosocial morbidity is undetected and untreated, with consequent exacerbated suffering, decreased satisfaction with care, impaired adherence to treatment regimens and poorer morbidity and mortality outcomes. The objective of this study is to develop, implement and assess the impact, acceptability and cost of an integrated, patient-centred Psychosocial Assessment, Care and Treatment (PACT) model of care for patients with urological and head and neck cancers. Methods and analysis: A time series research design will be used to test the PACT model of care, newly introduced in an Australian tertiary hospital. The primary outcome is system-level impact, assessed through audit of patients' medical records and Medicare claims for follow-up care. The secondary outcomes are impact of the model on patients' experience and healthcare professionals' (HCPs) knowledge and confidence, assessed via patient and HCP surveys at baseline and at follow-up. Acceptability of the intervention will be assessed through HCP interviews at follow-up, and cost will be assessed from Medicare and Pharmaceutical Benefits Scheme claims information and information logged pertaining to intervention activities (eg, time spent by the newly appointed psycho-oncology staff in direct patient contact, providing training sessions, engaging in case review) and their associated costs (eg, salaries, training materials and videoconferencing). Ethics and dissemination: Ethics approval was obtained from the Human Research Ethics Committees of Hunter New England Local Health District and the University of NSW. Results: The results will be widely disseminated to the funding body and through peer-reviewed publications, HCP and consumer publications, oncology conferences and meetings. Trial registration: The study is registered with the Australian New Zealand Clinical Trials Registry with registration number ACTRN12613000916741.